Effects of cannabidiol, with and without ∆9-tetrahydrocannabinol, on anxiety-like behavior following alcohol withdrawal in mice - Melkumyan, Mariam; Annaswamy, Vibha M.; Evans, Alexandra M.; Showemimo, Opeyemi F.; McCullers, Zari E.; Sun, Dongxiao; Murphy, Terrence E.; Vrana, Kent E.; Arnold, Amy C.; Raup-Konsavage, Wesley M.; Silberman, Yuval (Frontiers in Neuroscience, 2024)
Alcohol use disorder (AUD) is commonly associated with anxiety disorders and enhanced stress-sensitivity; symptoms that can worsen during withdrawal to perpetuate continued alcohol use. Alcohol increases neuroimmune activity in the brain, with our recent evidence indicating alcohol directly modulates neuroimmune function in the central amygdala (CeA), a key brain region regulating anxiety and alcohol intake, to alter neurotransmitter signaling. We hypothesized that cannabinoids, such as cannabidiol (CBD) and ∆9-tetrahydrocannabinol (THC), which are thought to reduce neuroinflammation and anxiety, may have potential utility to alleviate alcohol withdrawal-induced stress-sensitivity and anxiety-like behaviors via modulation of CeA neuroimmune function. Therefore, we tested the effects of CBD and CBD:THC (3:1 ratio) on anxiety-like behaviors and neuroimmune function in the CeA of mice undergoing acute (4-hr) and short-term (24-hr) withdrawal from chronic intermittent alcohol vapor exposure (CIE). We further examined the impact of CBD and CBD:THC on alcohol withdrawal behaviors in the presence of an additional stressor. We found that CBD and 3:1 CBD:THC increased anxiety-like behaviors at 4-hr withdrawal. At 24-hr withdrawal, CBD alone reduced anxiety-like behaviors while CBD:THC had mixed effects, showing increased center time indicating reduced anxiety-like behaviors, but increased immobility time that may indicate increased anxiety-like behaviors. These mixed effects may be due to altered metabolism of CBD and THC during alcohol withdrawal. Immunohistochemical analysis showed decreased S100 and Iba1 cell counts in the CeA at 4-hr withdrawal, but not at 24-hr withdrawal, with CBD and CBD:THC reversing alcohol withdrawal effects. These results suggest that the use of cannabinoids during alcohol withdrawal may lead to exacerbated anxiety depending on timing of use, which may be related to neuroimmune cell function in the CeA.